Solvent mediated synthesis of multicolor narrow bandwidth emissive carbon quantum dots and their potential in white light emitting diodes - Mohamed Sami; Mohamed E. El-Khouly; Mohsen Ghali (Scientific Reports)
Abstract The development of efficient and environmentally sustainable materials for white light-emitting diodes (WLEDs) is of paramount importance in the field of lighting technology. In this study, we present a solvent-modulated synthesis approach for the fabrication of multicolor narrow-bandwidth emissive carbon quantum dots (CQDs) as a promising solution for constructing WLEDs. The synthesis method involves the controlled reaction of organic precursors in different solvent environments, leading to the formation of CQDs with distinct emission wavelengths with a relatively small full width at half maximum, ranging from 28 to 42 nm. Moreover, these synthesized multicolor CQDs demonstrate a remarkably high fluorescence quantum yield of up to 65%, indicating their potential for constructing efficient WLED when incorporated in polymer matrix and coated on the surface of blue light-emitting diode (LED).